Transmission pipeline calculations and simulations manual - Menon, E. Shashi (Gulf Professional, 2015)
This manual is a valuable time- and money-saving tool that will help to quickly pinpoint essential formulae, equations, and calculations needed for transmission pipeline routing and construction decisions. Its three-part treatment starts with gas and petroleum data tables, followed by self-contained chapters concerning applications. Case studies at the end of each chapter provide practical experience for problem solving. Topics include: pressure and temperature profile of natural gas pipelines; how to size pipelines for specified flow rate and pressure limitations; calculating the locations and HP of compressor stations and pumping stations on long distance pipelines. -- Edited summary from book.
Keywords: Pipelines.; elektronické knihy; electronic books